DEVELOPING ENGLISH SPEAKING SKILL THROUGH THE USE OF BRAIN BASED TEACHING METHOD - Mahmudah, Dzur Rif'ah (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2016)
The objective of this research was to investigate whether the use of Brain Based Teaching Method could improve students’ speaking skill at the tenth graders of SMK Informatika Komputer Mahardika Makassar. The subjects in this research were students of X.A as an experimental group and X.B as a control group which was 40 students in total. This research was an experimental research which was consisted of pretest, treatment and posttest. The result of the t-test value in the pre-test between experimental group and control group (0.312) was lower than t-table (2.025) and r value (0.231) was higher than 0.05. So, in the pre-test there is not any significance difference between experimental group and control group. The result of the t-test value in the post-test between experimental group and control group (4.712) was higher than t-table (2.025) and r value (0.015) was lower than 0.05. That statement then proved that H1 was accepted which stated that there is a significance difference between students who was taught by using BBT with those who is taught by using Direct Instruction method. Based on the research findings above, the researcher could conclude that the use of Brain Based Teaching method was effective to develop the English speaking skill of X Students of SMK Informatika Mahardika Makassar.